Investigation into Low SAR PIFA Antenna and Design a Very Low SAR U-slot Antenna using Frequency Selective Surface for cell-phones and Wearable Applications - Kourosh Javadi; Nader Komjani (Emerging Science Journal, 2017)
There are very important questions. “Do Electromagnetic waves have irreparable effects on human or not?” “Are there any relation between cancer and waves?” and finally “what should we do to be safe?”. In the present article, these questions will be answered simply and professionally. First of all, Specific Absorption rate (SAR) is define then L-Slot and U-slot antenna is designed and simulated using cell-phones and wearable applications, operating at  and  consist of GSM900 and GSM1800. Standard frequency band width for the first and second band is  and  for uplink and downlink and in the present research these numbers are obtained. The SAR of each antenna is measured and is compared with each other. Thanks to design of antenna, The SAR of U-Slot antenna is very low and it is almost stimulated  and this sentence means this antenna is anti-cancer. Finally, Some SRR unit-cells are designed and when they are used in structure, SAR will be more decrease. Last SAR value is  and  for each bands .In the last table, There are some comparison between different creditable references and present article SAR reduction is acceptable and it is near to  percentage.